Ionic conductivity behavior by activated hopping conductivity (AHC) of barium aluminoborosilicate glass–ceramic system designed for SOFC sealing. Issue 10 (August 2019) - Da Silva, M.J.; Pontuschka, W.M.; Bartolomé, J.F.; Jasinski, P.; Karczewski, J.; Reis, S.T.
Abstract: Non-conducting BaO-B2 O3 -Al2 O3 -SiO2 parent glasses designed for solid oxide fuel cell (SOFC) sealing applications were prepared using the melt-quenching technique. The glass formation region was determined according to phase equilibrium relations and was found to be in the composition range 70BaO-( x )Al2 O3 -(10− x )B2 O3 -20SiO2 where 3.0 < x < 6.0 wt%. The conductivity values obtained conductivity ranged from 10 −5 to 10 −10 S/cm at temperatures between 600 and 850 °C. The batch compositions presented a threshold of dc conductivity near 70BaO wt% with a quasi linear behavior with the decrease of the BaO content. Different values of conduction activation energy were observed at temperatures above the glass transition temperature ( T g ) (up to 700 °C), which were attributed to the thermal bond-breaking of non-bridging oxygen (NBO) defects. The experimental results of the electrochemical characterization by impedance spectroscopy of glass–ceramic interfaces with yttria-stabilized zirconia (YSZ) acting as solid ionic conductor electrolyte are presented and discussed.